(3QhM GdeQjO aj TQM GdYbO GdaQjOs - (3eMeO Hf eMehO Hf eMeO GdSeQbfOjs; (3GdSeQbfOj , TeS GdOjf,J (B780 (3g` s
(3ChdgG (B:s
(3hHYO jbhd GdYHO GdVYja GdMGaX HcdGe Gddg GddWja eMeO GHf eMeO GdTQja GdSeQbfOj hGdbOQ hTQI ef Gddg s
(3BNQgG (B:s
(3hGddg MeOj OGFekG hESJYGfJj hEYJVGOi hEYJUGej JeJ GdcJGH HMQeI edc GdhgGH JeJ s
(3Vef eLehY , JQJjHgG (B: (3ef U (B126 - (3U(B133s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B87 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B4s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1152s
Keywords: (3GdbQGAGJ hGdJLhjOs